Comparison of native anatomy with recommended safe component orientation in total hip arthroplasty for primary osteoarthritis - Merle, Christian; Grammatopoulos, George; Waldstein, Wenzel; Pegg, Elise; Pandit, Hemant; Aldinger, Peter R.; Gill, Harinderjit S.; Murray, David W. (The journal of bone & joint surgery. A, American volume, 2013)
The adverse consequences of impingement, dislocation, and implant wear have stimulated increasing interest in accurate component orientation in total hip arthroplasty and hip resurfacing. The aims of the present study were to define femoral and acetabular orientation in a cohort of patients with primary hip osteoarthritis and to determine whether the orientation of their native hip joints corresponded with established recommendations for implantation of prosthetic components. - Methods: - We retrospectively evaluated a consecutive series of 131 preoperative computed tomography (CT) scans of patients with primary end-stage hip osteoarthritis (fifty-seven male and seventy-four female patients; mean age, sixty years). Patients were positioned according to a standardized protocol. Accounting for pelvic tilt, three-dimensional acetabular orientation was determined in the anatomical reference frame. Moreover, three-dimensional femoral version was measured. Differences in native anatomy between male and female patients were assessed with use of nonparametric tests. Native anatomy was evaluated with reference to the “safe zone” as described by Lewinnek et al. and to a “safe” combined anteversion of 20° to 40°. - Results: - In the entire cohort, the mean femoral anteversion was 13° and the mean acetabular anteversion was 19°. No significant differences in femoral, acetabular, or combined (femoral and acetabular) anteversion were observed between male and female patients. The mean acetabular inclination was 62°. There was no significant difference in acetabular inclination between female and male patients. We did not observe a correlation among acetabular inclination, acetabular anteversion, and femoral anteversion. Ninety-five percent (125) of the native acetabula were classified as being within the safe anteversion zone, whereas only 15% (nineteen) were classified as being within the safe inclination zone. Combined anteversion was within the safe limits in 63% (eighty-three) of the patients. However, only 8% (ten) of the cases in the present cohort met the criteria of both “safe zone” definitions (that of Lewinnek et al. and combined anteversion). - Conclusions: - Acetabular anteversion of the osteoarthritic hip as defined by the native acetabular rim typically matches the recommended component “targets” for cup insertion. There was no specific relationship among native acetabular inclination, acetabular anteversion, and femoral anteversion. Neither native acetabular inclination nor native combined anteversion appears to be related to current implant insertion targets. - Clinical Relevance: - The present findings of native acetabular and femoral orientation in patients with primary hip osteoarthritis support intraoperative component positioning for total hip arthroplasty.
Gesehen am 20.05.2021